Investigating the Molecular Basis for the Selective Inhibition of Aldehyde Dehydrogenase 2 by the Isoflavonoid Daidzin - da Silva Cunha, Thayssa Tavares; de Souza, Felipe Rodrigues; de Sena Murteira Pinheiro, Pedro; de Sant'Anna, Carlos Maurício Rabello; Noël, François; Costa França, Tanos Celmar; Manssour Fraga, Carlos Alberto (CNS & neurological disorders. Drug targets, 2020)
BACKGROUND: ALDH-2 has been considered an important molecular target for the treatment of drug addiction due to its involvement in the metabolism of the neurotransmitter dopamine: however, the molecular basis for the selective inhibition of ALDH-2 versus ALDH-1 should be better investigated to enable a more pragmatic approach to the design of novel ALDH-2 selective inhibitors. OBJECTIVE: In the present study, we investigated the molecular basis for the selective inhibition of ALDH-2 by the antioxidant isoflavonoid daidzin (IC50 = 0.15 μM) compared to isoform 1 of ALDH through molecular dynamics studies and semiempirical calculations of the enthalpy of interaction. METHODS: The applied methodology consisted of performing the molecular docking of daidzin in the structures of ALDH-1 and ALDH-2 and submitting the lower energy complexes obtained to semiempirical calculations and dynamic molecular simulations. RESULTS: Daidzin in complex with ALDH-2 presented directed and more specific interactions, resulting in stronger bonds in energetic terms and, therefore, in enthalpic gain. Moreover, the hydrophobic subunits of daidzin, in a conformationally more restricted environment (such as the catalytic site of ALDH-2), promote the better organization of the water molecules when immersed in the solvent, also resulting in an entropic gain. CONCLUSION: The molecular basis of selective inhibition of ALDH-2 by isoflavonoids and related compounds could be related to a more favorable equilibrium relationship between enthalpic and entropic features. The results described herein expand the available knowledge regarding the physiopathological and therapeutic mechanisms associated with drug addiction.
Keywords: Enzyme Inhibitors; dopamin; Isoflavones; Molecular Docking Simulation; Aldehyde Dehydrogenase; Dopamine; Substance-Related Disorders; inhibitory enzymů; vztahy mezi strukturou a aktivitou; poruchy spojené s užíváním psychoaktivních látek; isoflavony; aldehyddehydrogenasa; simulace molekulového dockingu; Structure-Activity Relationship